2015
DOI: 10.1002/2014jc010620
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic carbon system dynamics in landfast Arctic sea ice during the early‐melt period

Abstract: We present the results of a 6 week time series of carbonate system and stable isotope measurements investigating the effects of sea ice on air-sea CO 2 exchange during the early melt period in the Canadian Arctic Archipelago. Our observations revealed significant changes in sea ice and sackhole brine carbonate system parameters that were associated with increasing temperatures and the buildup of chlorophyll a in bottom ice. The warming sea-ice column could be separated into distinct geochemical zones where bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 64 publications
(131 reference statements)
3
41
0
Order By: Relevance
“…Peak ice algae Chl a concentrations in that study were relatively low (~20 mg/m 2 ), but there was a distinct pycnocline at ~50‐m depth, separating the polar mixed layer from underlying Pacific water. Conversely, Brown et al () saw no impact of ice algae on p CO 2sw in the water column through the peak of an intense bottom ice algae bloom near Resolute Bay, Nunavut. Ice algae concentrations in that study were much higher (max ~80 mg/m 2 ), but the water column in that region is typically mixed to the bottom (~150 m) due to strong tidally driven currents (Mundy et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…Peak ice algae Chl a concentrations in that study were relatively low (~20 mg/m 2 ), but there was a distinct pycnocline at ~50‐m depth, separating the polar mixed layer from underlying Pacific water. Conversely, Brown et al () saw no impact of ice algae on p CO 2sw in the water column through the peak of an intense bottom ice algae bloom near Resolute Bay, Nunavut. Ice algae concentrations in that study were much higher (max ~80 mg/m 2 ), but the water column in that region is typically mixed to the bottom (~150 m) due to strong tidally driven currents (Mundy et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…The reference ice concentration is set at 400 mmol C/m 3 , based on observed values of DIC for first‐year landfast sea ice near Resolute (generally in the range of 300–500 mmol C/m 3 ; cf. Brown et al, ; Geilfus et al, ). During ice formation, the average DIC concentration of seawater from which the ice is formed is near 2,100 mmol C/m 3 (Brown et al, ), and hence, DICSWref is set at 2,100 mmol C/m 3 .…”
Section: Methodsmentioning
confidence: 99%
“…In the polar oceans, ice cover further complicates the exchanges. Modelers have conventionally treated ice as an inert barrier to the exchange of CO 2 , but recent field work has shown that the growth and melt of sea ice can have a substantial impact on the transport of dissolved inorganic carbon (DIC) and total alkalinity (TA) in the surface polar oceans (e.g., Brown et al, ; Delille et al, ; Geilfus et al ; Miller, Carnat, et al, ; Miller, Papakyriakou, et al, ; Nomura et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall difference between photosynthesis and respiration represents net community production and describes whether sea ice may be considered as a net autotrophic (O 2 gain) or heterotrophic (O 2 loss) system [Codispoti et al, 2013]. The productive state of the biological community affects gas fluxes between the ice and ocean [Brown et al, 2015], as well as carbon cycling within the Arctic marine system [Matrai and Apollonio, 2013;Michel et al, 2015].…”
Section: Introductionmentioning
confidence: 99%